Study of Artificial Intelligent Algorithms Applied in Procedural Content Generation in Video Games - González-Hermida, Martín; Costa-Montenegro, Enrique; Legerén-Lago, Beatriz; Pena-Giménez, Antonio (Eludamos: Journal for Computer Game Culture, 2020)
-